(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
An adjective is a word that describes and gives information about the quality of nouns. They are used to let us imagine how something is. This article touches upon the topic adjectives in two Proto-Germanic languages English and German. This article provides the date about the position of adjectives in sentences, how they agree with nouns, agreeing with the case, person, singular and plural forms. Furthermore, this article looks at the origin of some adjectives in both languages, mainly the similarities, contrasts, different adjective suffixes and prefixes which build new adjectives from other parts of speech. The purpose of this study is to identify and give brief information about adjective suffixes, adjective buildings, the agreement of adjective and noun, types of adjectives